2015
DOI: 10.1016/j.fob.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Association between single nucleotide polymorphisms in MiR219‐1 and MiR137 and susceptibility to schizophrenia in a Chinese population

Abstract: HighlightsA case-control study investigated rs107822, rs1625579 and risk of schizophrenia.rs107822 was negatively associated with susceptibility to schizophrenia.No association was found between rs1625579 and the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Since our previous findings demonstrated that miR-219a over expression severely increases Scn5a expression [11], so we hypothesized that rs107822 within pri-miR-219a would affect its structure or expression, leading to an impaired miR-219a expression (most likely decreasing) which in turn will lead to a decreased SCN5A expression. Recently, Song et al demonstrated that the miR-219a rs107822 GA and AA genotypes decreased the mature miR-219a expression compared with the miR-219a rs107822 GG genotypes in normal tissues which further supports our hypothesis [34] Although the functionality of this polymorphism has been studied in several pathological contexts including cancers and psychological disorders [35,36], to our knowledge, it's the first time that the rs107822 is identified in patients with cardiac diseases particularly BrS.…”
Section: Discussionsupporting
confidence: 79%
“…Since our previous findings demonstrated that miR-219a over expression severely increases Scn5a expression [11], so we hypothesized that rs107822 within pri-miR-219a would affect its structure or expression, leading to an impaired miR-219a expression (most likely decreasing) which in turn will lead to a decreased SCN5A expression. Recently, Song et al demonstrated that the miR-219a rs107822 GA and AA genotypes decreased the mature miR-219a expression compared with the miR-219a rs107822 GG genotypes in normal tissues which further supports our hypothesis [34] Although the functionality of this polymorphism has been studied in several pathological contexts including cancers and psychological disorders [35,36], to our knowledge, it's the first time that the rs107822 is identified in patients with cardiac diseases particularly BrS.…”
Section: Discussionsupporting
confidence: 79%
“…A similar analysis carried out in patients with schizophrenia from Singapore has demonstrated a significant increase ( p = 0.016) in negative symptomatology in T/T patients compared to the subjects with G/G or G/T genotypes ( 8 ). Data obtained by three independent Chinese investigation groups showed no association of the studied locus with scores for PANSS subscales ( 14 , 16 , 25 ). Possibly, these controversial results may be explained by ethnical heterogeneity as well as the limited sample sizes.…”
Section: Discussionmentioning
confidence: 81%
“…A number of studies have reported an association between the SNPs in the MIR137 gene and the incidence of schizophrenia, with the T allele at the MIR137 SNP rs1625579 being most consistently associated with an increased risk of schizophrenia [ 56 , 57 , 58 , 59 ]. By contrast, some other studies have failed to show an association of any MIR137 SNPs and schizophrenia [ 60 , 61 , 62 ]. However, a meta-analysis of 12 case-control studies showed an association between rs1625579 and the incidence of schizophrenia, reporting that the T allele is associated with a 15% increase in the risk of developing schizophrenia compared to the G allele and that patients with the T/T genotype were at a 32% greater risk developing schizophrenia compared to those with the G/G genotype [ 63 ].…”
Section: Mir-137 In Schizophreniamentioning
confidence: 87%